Social Entrepreneurship As Seen By the Future Managers - Pereverzieva, Anna; Volkov, Volodymyr (International Journal of Scientific Research and Management (IJSRM), 2020)
Present society development faces a significant growth in unemployment in all countries around the world, regardless of the level of their development, and a decrease in income. Instability in the economy causes inability to meet population basic needs at the expense of available opportunities. There is a need to expand social entrepreneurship, launching of social enterprises, whose activities are based on innovative business models with a predominant focus on solving social problems. The entities` management requires training of management professionals able to deal with complex economic and social issues, rather than performing certain functions. The authors argue that it is the propensity / aversion to social entrepreneurship that determines the prospects for its development in a particular country. To test the hypothesis, a questionnaire was developed and a survey of students of different courses in economics and management was conducted. The questionnaire contained questions that allow us to consider the understanding of social entrepreneurship essence, the role of gender in social business, highlight key characteristics of social entrepreneurship and identify prospects for this innovative model through the propensity / aversion to social entrepreneurship.The study objective is to determine the propensity / aversion to social entrepreneurship in order to outline the future prospects for the formation of a new business model with value orientations on human resources. The results of the study demonstrated the importance of social entrepreneurship amid economic uncertainty and external threats. The vast majority of respondents have propensity and are ready to do business based on the innovative model of socially-oriented business. However, there is a fundamental belief in the psyche of people in economic benefits, but not the combination of social mission with efficiency, which is the basis of social business.The study could be a starting point for identifying areas to improve managers training through identification of key social orientations, which will help in the future to intensify the development of innovative business models aimed at solving socio-economic problems of a society.